Strain Bakteri Asam Laktat SBM10 dari Matriks Berbasis Nabati Berupa Fermentasi Sirup Beras Merah: Evaluasi Keamanan In Vitro dan Karakterisasi - Colin, Vito; Suandy, Suandy; Chiuman, Linda (Journal of Pharmaceutical and Sciences, 2025)
Plant-based fermentation offers a route to develop nondairy probiotic candidates, yet syrup-like matrices remain underexplored compared with solid or beverage systems. This study investigated fermented red rice syrup (prepared from red rice and barley malt powder) as a source of lactic acid bacteria (LAB) and advanced one isolate, SBM10. Cultivation on MRS supplemented with CaCO₃ yielded acidogenic colonies. A stable morphotype (SBM10) was purified and exhibited a LAB consistent profile, Gram-positive rods, catalase negative, TSIA K/A without H₂S, Simmons citrate negative, gelatinase negative, CO₂ positive in Durham and γ-hemolytic on 5% sheep blood agar. Under gastrointestinal stress models (4 h, 37 °C), tolerance relative to controls was 27.14% at pH 3.0 and 35.58% in 0.3% oxgall. In disk diffusion assays, the cell-free supernatant (CFS) showed no inhibition of Escherichia coli or Staphylococcus aureus. Thus, no antibacterial activity was detected by disk diffusion under the conditions tested, whereas amoxicillin produced zones of 13.95 mm and 12.43 mm, respectively. SBM10 presents a safety-supportive, LAB-typical profile with partial tolerance to gastric-like acidity and bile. Although no disk diffusion antagonism was detected for the CFS, the results motivate taxonomic confirmation and process/formulation optimization, such as improving acid/bile robustness and re-evaluating antimicrobial potential with complementary assays, to clarify the suitability of SBM10 for plant-based functional applications.